Improved polyphenol extraction thanks to ultrasounds.
With ULTRAWINE, Spanish SME AGROVIN promises a piece of revolutionary ultrasound equipment for wineries, one that will accelerate the grape maceration process and reduce energy use drastically-all this whilst guaranteeing great wine colouration and quality.